2018
DOI: 10.1111/desc.12737
|View full text |Cite
|
Sign up to set email alerts
|

Dissociable spatial memory systems revealed by typical and atypical human development

Abstract: Rodent lesion studies have revealed the existence of two causally dissociable spatial memory systems, localized to the hippocampus and striatum that are preferentially sensitive to environmental boundaries and landmark objects, respectively. Here we test whether these two memory systems are causally dissociable in humans by examining boundary- and landmark-based memory in typical and atypical development. Adults with Williams syndrome (WS)-a developmental disorder with known hippocampal abnormalities-and typic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 62 publications
0
12
0
Order By: Relevance
“…Response learning has been shown to be facilitated in the presence of hippocampal dysfunction (9). In our response learning task, individuals with DS and individuals with WS exhibited better performance than MA-matched TD children, suggesting that the neurobiological substrates subserving response learning are relatively intact in these two syndromes and that impaired hippocampal function contributes to improved performance in striatal-dependent tasks in these individuals (36,37,70).…”
Section: Response Learningmentioning
confidence: 82%
“…Response learning has been shown to be facilitated in the presence of hippocampal dysfunction (9). In our response learning task, individuals with DS and individuals with WS exhibited better performance than MA-matched TD children, suggesting that the neurobiological substrates subserving response learning are relatively intact in these two syndromes and that impaired hippocampal function contributes to improved performance in striatal-dependent tasks in these individuals (36,37,70).…”
Section: Response Learningmentioning
confidence: 82%
“…If OPA supports visually guided navigation and matures late in childhood, then we should also predict that children's visually guided navigation abilities to mature late in development. Consistent with this idea, a recent study investigated the development of spatial memory relative to boundaries using a task known to depend on OPA by adulthood ( Julian et al, 2016) and found protracted development late into childhood ( Julian et al, 2019). Furthermore, unlike adults, younger children are poorer at utilizing peripheral cues while navigating (Franchak & Adolph, 2010) and make more errors in obstacle avoidance and path-following tasks (Berard & Vallis, 2006).…”
Section: Moving Beyond Scene Selectivitymentioning
confidence: 85%
“…Third, and finally, the limited available evidence nevertheless supports the idea of protracted development of visually guided navigation. For example, as alluded to earlier, navigation-related skills, including locomotion (Franchak & Adolph, 2010), obstacle avoidance (Berard & Vallis, 2006), and boundary-based spatial memory (Julian et al, 2019), appear to undergo protracted developmental trajectories, still developing as late as 8 years old. By contrast, scene recognition abilities appear early in life—even infants can recognize scene information (i.e., discriminating whether a cliff is deep or shallow) long before they can independently move around their surroundings (e.g., by crawling; Campos et al, 1970).…”
Section: A Novel Hypothesis: Visually Guided Navigation and Map-based...mentioning
confidence: 91%
“…To study how navigationally relevant information processing develops in the occipital place area (OPA), we measured responses in OPA across childhood to first-person perspective motion-a proxy for the visual experience of actually navigating through an immediately visible scene. Given previous findings that boundary-based navigation and other dorsal stream processes are still developing in childhood [14][15][16], we scanned two groups of children: 5 year olds and 8 year olds. Responses in OPA were measured using functional magnetic resonance imaging (fMRI) while participants viewed (1) 3-s video clips of firstperson perspective motion through scenes (''dynamic scenes''), mimicking the actual visual experience of visually guided navigation, and (2) 3 1-s still images taken from these same video clips, rearranged such that first-person perspective motion could not be inferred (''static scenes'').…”
Section: Resultsmentioning
confidence: 99%